Removal of nickel and iron from contaminated water by using magnetic separation / Nurulhuda Kassim - Kassim, Nurulhuda (Faculty of Applied Sciences, 2009)
Environmental constraints have forced industry to reduce their emission of heavy metal that could cause severe environmental problem. There is thus a need for new, more effective method. Magnetic separation offers a good solution for cleaning contaminated water. The aim of this project is to determine the efficiency of magnetic separation method. The research was focused on removing Nickel and Iron contained in contaminated water. This method consist of the usage of magnet powder, NdFeB and magnet bar applied with the varied amount (5g ,10g ,15g) of magnet powder and was tested in (100ml and 500ml) sample. The initial and the final concentration of sample was determined by using AAS.As a result, this method gives more than 85% efficiency for both Nickel and Iron. With the increasing amount of magnet powder used, the efficiency also increased. In a conclusion, this method has a high efficiency in removing Nickel and Iron in contaminated water.